Debit, Credit, and Input-Output Tables. - Goetz, Billy E.; Churchill, Neil C. (The Accounting Review, 1967)
This article focuses on the use of computer-assisted instruction for the computation of debit and credit accounting. As financial transactions occur, documents are prepared and filed in the usual way. Each transaction is analyzed into one or more pairs of equal debits and credits. Each such pair is entered in a magnetic tape as four numbers: a file number, the number of the account debited, the number of the account credited, and the dollar amount. The tape is fed into the computer, which is programmed to ignore the file number, to choose the table row headed by the debited account's number and the column headed by the credited account's number, and to add the dollar amount to the total in the cell thus designated. National income accounting was created on the enterprise accounting model. It was vigorously developed by economists and statisticians, who converted the double-entry accounts and trial balances into input-output tables of the national economy.